1999
DOI: 10.1097/00000658-199905000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Protein Catabolism After Severe Burn: Effects of IGF-1/IGFBP-3 Treatment

Abstract: ObjectiveTo determine the effects of recombinant human insulin-like growth factor-1 (IGF-1) complexed with its principal binding protein, IGFBP-3, on skeletal muscle metabolism in severely burned children. Summary Background DataSevere burns are associated with a persistent hypermetabolic response characterized by hyperdynamic circulation and severe muscle catabolism and wasting. Previous studies showed that nutritional support and pharmacologic intervention with anabolic agents such as growth hormone and insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(89 citation statements)
references
References 18 publications
(24 reference statements)
3
84
0
2
Order By: Relevance
“…The IGF-I system is synthesized in the liver and its production is stimulated by GH (131)(132)(133). IGF-I has been shown to improve cell recovery, muscle protein synthesis, gut and immune function, and exert promitogenic functions not only after burn, but also in various other pathological states (7,(134)(135)(136)(137). Recent evidence suggests that IGF-I is instrumental in the early phases of liver regeneration after trauma and modulates the hepatic acute phase response in burned rats restoring hepatic homeostasis and improving hepatic morphology (136,137).…”
Section: Hormonesmentioning
confidence: 99%
“…The IGF-I system is synthesized in the liver and its production is stimulated by GH (131)(132)(133). IGF-I has been shown to improve cell recovery, muscle protein synthesis, gut and immune function, and exert promitogenic functions not only after burn, but also in various other pathological states (7,(134)(135)(136)(137). Recent evidence suggests that IGF-I is instrumental in the early phases of liver regeneration after trauma and modulates the hepatic acute phase response in burned rats restoring hepatic homeostasis and improving hepatic morphology (136,137).…”
Section: Hormonesmentioning
confidence: 99%
“…1,2 The prolonged post-traumatic hypermetabolic state has been attenuated by aggressive nutritional and pharmacologic interventions. [3][4][5] The release of pro-inflammatory cytokines after severe trauma occurs not only at a systemic level but also in the burn wound itself and to a lesser extent in the surrounding uninjured tissue. 6,7 The skin constitutes the body's largest immune organ, thus a thermal injury clearly influences immune competence and resistance against infection and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Agents known to affect postburn hypermetabolism and catabolism are insulin, IGF-I, oxandrolone, GH, and propranolol. 4,18,[30][31][32][33] As GH increases mortality in critically ill adults 34 and IGF-I is at the moment limited in its availability, we recommend the use of insulin, oxandrolone, or propranolol to attenuate hypermetabolism and catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we conducted an animal and a clinical study in which we showed that IGF-I, in combination with its principle binding protein, improved muscle protein synthesis, hepatic acute phase and inflammatory response, and immune system. 30,32,50 However, we suggest that it would be necessary to test IGF-I in a large multicenter trial to determine whether IGF-I would be a beneficial treatment option in severely burned patients.…”
Section: Discussionmentioning
confidence: 99%